Determining Solar Energy Power System Potentials for Electrification Using the Angstrom-Prescott Equation in Benue State - Iortim, Dennis Mkur; Nyam, George Gala; Tsoho, Ibrahim Yakubu; Umar, Medina (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
Using MATLAB R2020, the Angstrom-Prescott equation was created for a simple five-year forecast of Makurdi town's solar radiation values: H/Ho = 0.166 + 0.578(n/N). The values of "a" and "b," which were found to be 0.166 and 0.578, respectively, demonstrated a sharp increase in Makurdi town's exposure to sunlight (temperature) and solar radiation. Although this increase indicated a high degree of global warming effects in this research area, it also opened up significant possibilities for solar power generation for universal electrification, which would help to lessen the impact of global warming in this area (Makurdi). Using the Coefficient of Determination (R2) and the Root Mean Square Error (RMSE) as 0.704 (70.4%) and 0.148 (14.8%), respectively, the research work's produced results were statistically tested.